2013
DOI: 10.1016/j.jmbbm.2013.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of the human enamel fracture toughness with aging

Abstract: Enamel AgingMineral content a b s t r a c t A better understanding of the fracture toughness (KIC) of human enamel and the changes induced by aging is important for the clinical treatment of teeth cracks and fractures. We conducted microindentation tests and chemical content measurements on molar teeth from "young" (18≤age≤25) and "old" (55≤age) patients. The KIC and the mineral contents (calcium and phosphorus) in the outer, the middle, and the inner enamel layers within the cuspal and the intercuspal regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…Specifically, when fracture toughness and crack growth were measured, the inner enamel closer to the DEJ was found to be tougher and to resist crack propagation more than outer enamel (18,19). A positive contribution by the EOM was shown by a reduction in fracture toughness after its removal or alteration (20,21).…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, when fracture toughness and crack growth were measured, the inner enamel closer to the DEJ was found to be tougher and to resist crack propagation more than outer enamel (18,19). A positive contribution by the EOM was shown by a reduction in fracture toughness after its removal or alteration (20,21).…”
Section: Discussionmentioning
confidence: 98%
“…Obtained findings indicated that the teeth having EMCs from the older age group possessed higher width and length values compared with the younger one. Aging and the related changes in the mechanical properties of human enamel (increase in hardness, elastic modulus, brittleness, and decrease in fracture toughness with age) might explain the aforementioned difference 25,29,30) . Further analysis revealed that following debonding width and length of all EMCs increased.…”
Section: Discussionmentioning
confidence: 99%
“…While there were differences between FEA and MPS results in terms of oscillations resulting from the two different approaches as described by Eqs. (15) and (16) for discretization of the continuum model in Eq. (1), the trends observed were remarkably similar for most of the parameters evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the MPS has been extended to the non-linear elastodynamics of compressible and incompressible materials such as viscosity in enamel [14]. When compared with FEA, MPS has the distinct advantage of being a mesh free model, which is more suited to deformation analysis and to simulation of complex material properties such as interprismatic organic matrix of enamel [15]. A current limitations of the MPS method is that to date there have been no systematic comparative studies with FEA.…”
Section: Introductionmentioning
confidence: 99%